Design of enamides as new selective monoamine oxidase-B inhibitors. (3rd April 2020) - Kavully, Fathima Sahla; Oh, Jong Min; Dev, Sanal; Kaipakasseri, Swafvan; Palakkathondi, Ashique; Vengamthodi, Ajeesh; Abdul Azeez, Rinshana Fathima; Tondo, Anna Rita; Nicolotti, Orazio; Kim, Hoon; Mathew, Bijo
Abstract: Objectives: To develop of new class of selective and reversible MAO-B inhibitors from enamides. Methods: Syntheses of the titled derivatives (AD1–AD11 ) were achieved by reacting cinnamoyl chloride and various primary and secondary amines in basic medium. All eleven compounds were investigated for in vitro inhibitory activities against recombinant human MAO-A and MAO-B. The reversibilities of lead compound inhibitions were analysed by dialysis. MTT assays of lead compounds were performed using normal VERO cell lines. Key findings: Compounds AD3 and AD9 exhibited the greatest inhibitory activity against MAO-B with IC50 values of 0.11 and 0.10 µm, respectively, and were followed by AD2 and AD1 (0.51 and 0.71 µm, respectively). Most of the compounds weakly inhibited MAO-A, with the exceptions AD9 and AD7, which had IC50 values of 4.21 and 5.95 µm, respectively. AD3 had the highest selectivity index (SI) value for MAO-B (>363.6) and was followed by AD9 (SI 42.1). AD3 and AD9 were found to be competitive inhibitors of MAO-B with Ki values of 0.044 ± 0.0036 and 0.039 ± 0.0047 µm, respectively. Reversibility experiments showed AD3 and AD9 were reversible inhibitors of MAO-B; dialysis restored the activity of MAO-B to the reference level. MTT assays revealed AD3 and AD9 were non-toxic to normal VERO cell lines with IC50 values of 153.96 and 194.04 µg/ml, respectively. Computational studies provided hypothetical binding modes for AD3 and AD9 in the binding cavities of MAO-A and MAO-B. Conclusions: These results encourage further studies on the enamide scaffold as potential drug candidates for the treatment of Alzheimer's and Parkinson's diseases.